5G MEC system security capability deployment scheme - Yunyi LIU; Jianmin ZHANG; Xiaoli FENG; Liwei ZHANG (Dianxin kexue)
Multi-access edge computing (MEC), as the core differentiated capability of 5G, is the key technology for telecom operators to build private 5G networks for enterprises.With the increase of 5G MEC nodes, security risks and protection schemes are increasingly concerned.Based on the description of 5G MEC system architecture, the potential security risks were analyzed.On this basis, the security capability deployment architecture and scheme of the 5G MEC system were proposed, and the deployment case was introduced.Finally, the current problems and challenges in the deployment of MEC security capabilities were discussed to provide references for subsequent research and development.